Interorganizational Information System Deployment in Supply Chain Triads - Bodendorf, Frank; Schmidt, Lars; Franke, Jörg (International Conference on Information Systems, ICIS 2023: "Rising like a Phoenix: Emerging from the Pandemic and Reshaping Human Endeavors with Digital Technologies", 2023)
Interorganizational information systems (IOIS) are valuable tools providing platforms for information flow enabling more efficient and reliable collaboration in digitalized supply chains. An IOIS is subject to influencing factors originating in the company and environment. Inspired by complex adaptive system theory, an agent-based simulation model is designed, exploring factors affecting the integration and efficiency of IOIS. These factors are derived from resource-based view and dynamic capabilities theory. The influence on information system deployment is assessed by merging these factors into exogenous, intercompany climate, and operational dimensions. First, the results indicate that product-specific factors have a greater influence than the environment when deploying an IOIS. Second, deliberate design of IC relationships should be considered during the development of an IOIS. Third, extensive information exchange between supply chain partners might be disadvantageous for IOIS utilization. Fourth, the advantages of IOIS can be lost when completely open systems are used.
CRIS-Team Scopus Importer:2024-12-16
Keywords: agent-based modeling; complex adaptive systems; Interorganizational information systems; supply chain management